Effect of tea tree oil on candida adherence and surface roughness of heat cure acrylic resin - Zahraa S Noori; Aseel M Al-Khafaji; Fatemeh Dabaghi (College of Dentistry/ University of Baghdad, 2023)
Background: Denture cleansing was an important step that could prevent the spread of infection and improve a patient's health, the durability of the dentures, and the overall quality of life; therefore, it was necessary to choose a suitable cleanser that, in addition to being effective, did not have an unfavorable effect on the qualities of the denture base resin itself when used for an extended period. For this purpose, this study aimed to evaluate the effect of tea tree oil (TTO) on Candida albicans adhesion and the surface roughness property of poly(methyl methacrylate) denture material after immersion in TTO. Methods: A total of 55 heat-cured acrylic resin specimens were used for C. albicans adherence and surface roughness tests. They were distributed into groups (0.25%, 0.5%, 0.75%, and 1%) of TTO, distilled water (DW), and 2% clorhexidine digluconate, totaling five specimens for each group. The specimens were immersed in accordance with their group for 10 minutes. Surface roughness was determined by a profilometer, and C. albicans adherence was determined by measuring optical density with a spectrophotometer. For comparisons between groups for surface roughness and disinfection tests, one-way ANOVA was performed on SPSS program, considering α = 0.05. Results: TTO had a statistically significant effect on C. albicans adhesion to heat-cured acrylic resin (P < 0.05) compared with negative control. Meanwhile, no statistically significant difference was found between 0.75% and 1% TTO concentrations (P > 0.05), whereas the surface roughness test showed a statistically non-significant difference between TTO concentrations and DW (P > 0.05). Conclusions: Immersion of acrylic resin in TTO was effective in decreasing C. albicans adhesion to it, and the greatest decrease was obtained by 1% TTO. The surface roughness test showed a non-significant difference in acrylic roughness after immersion in TTO.